Reflections About the Role of Intellectuals in Latin America - Naidorf, Judith; Martinetto, Alejandra Beatriz; Sturniolo, Silvina Andrea; Armella, Julieta (Education Policy Analysis Archives, 2010)
The purpose of this paper is to address some theoretical aspects - concepts that contribute to reflection on the specific role of the current Latin American intellectual. The contributions of various authors will help us to characterize a role that is constantly rethinked, analyzed and disputed. The proposal is to retake the theoretical developments in the category "intellectual" from Antonio Gramsci and Immanuel Wallerstein mainly, but making reference to its most intense moments in the 60-70 decades with Sartre and Foucault in Europe. It also highlights the contributions made by Pierre Bourdieu, Sousa Santos and the contributions to Latin America by Fals Borda, Florestan Fernandez, Octavio Ianni and Eliseo Veron, among others. Also included are examples of statements for the EZLN by Subcomandante Marcos and refers to the analysis performed by Julio Gambina and Daniel Campione for the Argentine case. It’s not the interest of this work to arrive at definitions finished about the social function of intellectual debate but to contribute to a not new but always applicable, which should be a breakthrough for each of our practices in the different social areas in which we daily work.